2020
DOI: 10.1155/2020/4065207
|View full text |Cite|
|
Sign up to set email alerts
|

Emotion Recognition of Students Based on Facial Expressions in Online Education Based on the Perspective of Computer Simulation

Abstract: Online education has developed rapidly due to its irreplaceable convenience. Under the severe circumstances caused by COVID-19 recently, many schools around the world have delayed opening and adopted online education as one of the main teaching methods. However, the efficiency of online classes has long been questioned. Compared with traditional face-to-face classes, there is a lack of direct, timely, and effective communication and feedback between teachers and students in the online courses. Previous studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(21 citation statements)
references
References 54 publications
0
21
0
Order By: Relevance
“…Delivery of classes using online platform has been popular since the Covid19. In [31], facial expression based ERS is used to measure the students' reaction towards the end of an online meeting to overcome the lack of communication between the students and instructor.…”
Section: Emotion Recognition System In Educationmentioning
confidence: 99%
“…Delivery of classes using online platform has been popular since the Covid19. In [31], facial expression based ERS is used to measure the students' reaction towards the end of an online meeting to overcome the lack of communication between the students and instructor.…”
Section: Emotion Recognition System In Educationmentioning
confidence: 99%
“…Automatic Face Analysis (AFA) system was developed by (Tian, et (Yang et al, 2017) proposed a learning emotion recognition model consisting of feature extraction, subset feature and emotion classifier. In the work of Wang et al (2020), the framework of FER algorithm was combined with online courses platforms using computer simulation to recognise student's emotion in an online education. Shuaibu et al (2018) fused PCA and LBP with sparse coding to achieved FER using the linear kernel multi-class support vector machine (LSVM) classifier.…”
Section: Related Workmentioning
confidence: 99%
“…he classification of human facial expressions which include surprise, happiness, anger, contempt, disgust, fear is a process known as facial expression recognition (FER) (Shuaibu, et al 2018). Facial expression is used by humans irrespective of their nationality, sex or race to express their states of emotion and what they intent (Wang, et al 2020). Despite the FER process, recognition of the face remains a difficult task due to variations of the face that are caused by aging, varying illumination, pose etc.…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies address problems in the use of distance education for various reasons. For instance, W. Wang et al (2020) and Hodges et al (2020) confirmed the existence of a physical gap between the teacher and the learners due to the application of distance education, which had a role in limiting the building of relationships between these two basic elements in the educational process (Cakula et al, 2016). Some studies noted that distance education would not yield completely positive results without a very high degree of self-discipline (Al-Abdullatif et al, 2020;Augner et al, 2012;Lee et al, 2016).…”
Section: Introductionmentioning
confidence: 99%